Hierarchically assembled ZnO nanosheets microspheres for enhanced glucose sensing performances. Issue 12 (September 2016) - Ahmad, Rafiq; Tripathy, Nirmalya; Khan, Muhammad Yasir; Bhat, Kiesar Sideeq; Ahn, Min-sang; Khang, Gilson; Hahn, Yoon-Bong
Abstract: Nanostructures with higher surface specific area has great potential applications in sensing devices because higher surface specific area not only improve protein/enzyme immobilization efficiency, but also enhances charge transport and sensing performances. Herein, hierarchically assembled ZnO nanosheets microspheres (HAZNMs) were synthesized by facile one-pot solution process at low-temperature. Results showed that as-synthesized HAZNMs possessing higher specific surface area, significantly increased the enzyme loading efficiency which in turn improved the sensing performances. The as-fabricated biosensors showed a remarkably high sensitivity (210.8 μA/mM cm 2 ) in the wide-linear response range of 0.05–23 mM, favorable stability for long-term storage, excellent anti-interference ability and high reliability for glucose detection in human blood serum samples. The improved sensing performances can be ascribed to the high glucose oxidase (GOx) enzyme immobilization on HAZNMs that provides a favorable microenvironment for the maintenance of GOx enzyme bioactivity.